Develpoment of combinatorial optimisation for cutting tool path strategy - Alsultaney, Hazem K.; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Ali, Aidy; Mustapha, Faizal (2009)
This work aims to optimise the tool path by simulating the removal of material in a finite element environment, which is controlled by a Genetic Algorithm. To simulate the physical removal of material during machining, a finite element model is designed to represent a thin walled workpiece. The target was to develop models which mimic the actual cutting process using the Finite Element Method (FEM) and to validate the developed tool path strategy algorithm with the actual machining process and to programmer the developed algorithm into software. The workpiece has to be modeled using the CAD (ABAQUS CAE) software in order to create a basic geometry co-ordinate system which then is used to create the FE element and necessary requirement by ABAQUS, such as the boundary condition, the material type, and the element type.